GASTRORETENTIVE DRUG DELIVERY SYSTEM - A REVIEW - RIZWANA KHAN (International Journal of Pharma and Bio Sciences, 2013)
Oral delivery of drugs is by far the most preferable route of drug delivery . Oral-rate controlled drug delivery systems have an important area among novel drug delivery system. But these oral sustained release drug delivery systems suffer greatly due to their short gastric residence time/ gastric emptying time. Whereas prolonged gastric residence increases duration of drug release, reduces drug waste, and improves drug solubility in gastric pH. In order to overcome these drawbacks novel dosage forms that can be retained in the stomach for a prolonged and predictable period of time were discovered and they successfully exists today as gastroretentive dosage forms, in academic and industrial research groups. The aim of writing this review on gastroretentive drug delivery system was to present the recent literature in a more concise way with special focus on various techniques to achieve gastric retention. In addition, important factors controlling gastroretention, advantages,analysis techniques and finally, future potentials are also discussed.